Resiliensi Istri yang Dipoligami: Studi Kasus Poligami di Desa Rombiya Timur Kabupaten Sumenep - Mukammilah, Mu'izzatul (Universitas Muhammadiyah Jember, 2021)
The practice of polygamy has both negative and positive effects. But for polygamous wives, the negative effects are felt more than the positive effects. The purpose of this study was to describe the resilience of a polygamous wife and the internal and external factors that influence it. The internal factors that form resilience refer to the theoryÂ forward by Reivich Shatte that there are 7 aspects of resilience, namely emotional regulation, impulse control, optimism, empathy, analysis of causes of problems, self-efficacy and reaching out. This research uses a qualitative approach with a case study method. Participants in the study were 3 people who were selected using purposive sampling technique with the following characteristics: 1) A woman who is the first wife of a polygamous husband. 2) Still having legal status as wife. 3) Do not know when the polygamy happened. The data collection method uses in-depth interview techniques. The results of this study indicate that the three participants can be resilient by fulfilling 7 aspects of resilience, and their resilience is also influenced by external factors in the form of support from family and the environment.